Interleukin-15 selectively expands CD57+ CD28- CD4+ T cells, which are increased in active rheumatoid arthritis - Yamada, Hisakata (Clinical immunology (Orlando, Fla.), 2007)
Proinflammatory cytokines as well as CD4(+) T cells play critical roles in the pathogenesis of rheumatoid arthritis (RA). Recently, an increase of CD57(+) or CD28(-)CD4(+) T cells was demonstrated in RA, although the mechanism of the increase of these T cells is unclear. In this study, we first examined the relationship between CD57(+)CD4(+) T cells and CD28(-)CD4(+) T cells and found CD57(+)CD28(-)CD4(+) T cells, but neither CD57(+)CD28(+) nor CD57(-)CD28(+) cells, expanded in the peripheral blood of active RA. In vitro experiments revealed that CD57(+)CD28(-)CD4(+) T cells selectively expanded in response to IL-15. Furthermore IL-15-stimulated CD57(+)CD28(-)CD4(+) T cells induced TNF-alpha production from monocytes. These results suggest that CD57(+)CD28(-)CD4(+) T cells are involved in the pathogenesis of RA by responding to IL-15